Synthetic hydrogels as blood clot mimicking wound healing materials. (30th September 2021) - Rausch, Manuel K.; Parekh, Sapun H.; Dortdivanlioglu, Berkin; Rosales, Adrianne M.
Abstract: Excessive bleeding—or hemorrhage—causes millions of civilian and non-civilian casualties every year. Additionally, wound sequelae, such as infections, are a significant source of chronic morbidity, even if the initial bleeding is successfully stopped. To treat acute and chronic wounds, numerous wound healing materials have been identified, tested, and adopted. Among them are topical dressings, such as gauzes, as well as natural and biomimetic materials. However, none of these materials successfully mimic the complex and dynamic properties of the body's own wound healing material: the blood clot. Specifically, blood clots exhibit complex mechanical and biochemical properties that vary across spatial and temporal scales to guide the wound healing response, which make them the ideal wound healing material. In this manuscript, we review blood clots' complex mechanical and biochemical properties, review current wound healing materials, and identify opportunities where new materials can provide additional functionality, with a specific focus on hydrogels. We highlight recent developments in synthetic hydrogels that make them capable of mimicking a larger subset of blood clot features: as plugs and as stimuli for tissue repair. We conclude that future hydrogel materials designed to mimic blood clot biochemistry, mechanics, and architecture can be combined with exciting platelet-like particles to serve as hemostats that also promote the biological wound healing response. Thus, we believe synthetic hydrogels are ideal candidates to address the clear need for better wound healing materials.